Influence of Funding Sources and Business Diversification on the Financial Performance of Regional Water Company Jayapura Regency - -, Mugiati (Information Management and Business Review, 2016)
To examine and analyze the influence sources of funding consisting of long-term debt and capital to diversification business and financial performance of Regional Water Company Jayapura Regency. Methods of collecting data used were observation, interviews and secondary data such as financial statements and other documents that have to do with research. Data were analyzed descriptively and quantitatively using the financial ratio analysis, Du Pont analysis and financial ratios specified by Decree 47 of 1999. The results showed that: the effect on the long-term debt diversification Regional Water Company Jayapura regency primarily on the acquisition of Long-Term Debt laba. Dan also affect the financial performance of Regional Water Company redgional Water Company Jayapura regency precisely at the level of solvabilitas, where based on research results Regional Water Company Jayapura Regency has a high level of solvabilitas, high solvabilitas is caused by injection of funds from the government charged as long-term debt. The use of equity capital effect on business diversification and financial performance of the Regional Water Company Jayapura regency. This is evidenced by a decrease in profit resulting from lower equity and the amount of long-term debt. Which due to the lack of balance between long-term debt and equity. And diversification efforts affect the financial performance of the Regional Water Company Jayapura Regency